Lipidomic signatures in Octopus vulgaris arm muscle reveal geographic variation along the Iberian Atlantic Coast - Felisa Rey; Luís Gaspar; Fernando Ricardo; Cristina Pita; Maria do Rosário Domingues; Ricardo Calado (npj Science of Food)
Abstract The common octopus (Octopus vulgaris) is a highly valued seafood species, whose flavour and palatability are often linked to its geographic origin. However, globalized supply chains have increased the risk of mislabelling. Lipid metabolism in marine organisms is shaped by environmental conditions, then lipidomics offers a promising tool for origin authentication. This study used HILIC-LC-MS&MS/MS to profile the polar lipidome of O. vulgaris arm muscle from three Iberian Atlantic landing sites: Ría de Arousa (Spain), Peniche, and Santa Luzia (Portugal). While total lipid content was consistent across sites, Peniche samples showed lower phospholipid levels, and Santa Luzia samples showed elevated LPE/PE and LPC/PC ratios, possibly reflecting stress or degradation. Ether-linked phospholipids and the sphingolipid CAEP were most abundant in Ría de Arousa, contributing to site discrimination. These findings demonstrate the potential of lipidomic profiling as a tool for seafood traceability, offering insights into environmental and dietary influences on lipid composition.